Pengembangan Komik Strip Digital Berbasis Isu-Isu Kebahasaan di Sekitar untuk Meningkatkan Literasi Siswa - Yohanna Nirmalasari (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
ABSTRACT Comic strips are a concise narrative form using images to convey messages briefly. They help students understand concepts and increase learning motivation, particularly in addressing contemporary linguistic issues. While comic strips are commonly used in subjects like science, history, and religion, their use in language learning, especially at the student level, is still rare. However, comics are effective and enjoyable for learners of all ages. This research aims to develop comic strip learning media for Indonesian language education. The ADDIE development method was applied, with the media covering eight chapters: the position and function of Indonesian language, language variety, spelling, punctuation, effective sentence construction, discourse, scientific writing, and citation and reference formatting. Based on the research findings, it was concluded that comic strips can help students better understand literacy activities, especially in critically analyzing linguistic issues in their environment. This study highlights that incorporating comic strips into language education can boost student engagement and comprehension, making the learning process both enjoyable and effective. Keywords: Comic Strips; Linguistic Issues; Literacy; Media Development